2012
DOI: 10.1002/gcc.21945
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ALKPTPN3 gene fusion from human non‐small cell lung carcinoma cell line using next generation RNA sequencing

Abstract: An increasing number of chromosomal aberrations is being identified in solid tumors providing novel biomarkers for various types of cancer and new insights into the mechanisms of carcinogenesis. We applied next generation sequencing technique to analyze the transcriptome of the non-small cell lung carcinoma (NSCLC) cell line H2228 and discovered a fusion transcript composed of multiple exons of ALK (anaplastic lymphoma receptor tyrosine kinase) and PTPN3 (protein tyrosine phosphatase, nonreceptor Type 3). Deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 14 publications
1
47
0
1
Order By: Relevance
“…The key net result appears to be the null mutation of one allele of PTPN3, a gene with tumor suppressor activity. Consistently, ectopic expression of PTPN3 in NSCLC cell lines led to inhibition of colony formation (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The key net result appears to be the null mutation of one allele of PTPN3, a gene with tumor suppressor activity. Consistently, ectopic expression of PTPN3 in NSCLC cell lines led to inhibition of colony formation (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Several alternatively spliced transcript variants encoding different isoforms have been found for this gene. Jung et al (2012) applied the next-generation sequencing technique to analyze the transcriptome of the non-small cell lung carcinoma (NSCLC) cell line H2228, and discovered a fusion transcript composed of multiple exons of anaplastic lymphoma receptor tyrosine kinase (ALK) and PTPN3. Detailed analysis of the genomic structure revealed that a portion of the genomic region encompassing exons 10 and 11 of ALK has been translocated into the intronic region between exons 2 and 3 of PTPN3.…”
Section: Discussionmentioning
confidence: 99%
“…Variants v1, v2, v3a and v3b of EML4-ALK fusion gene are the most commonly detected, together accounting for more than 90% of variants in some series (20). Although more uncommon, other ALK fusion partners have been identified as TFG (TRK-fused gene), KIF5B, PTPN3 and KLC1 (21)(22)(23). The different EML4 variants and the further partner genes do not seem to significantly impact on biology and sensitivity of ALK-rearranged malignant cells and tumors to specific inhibitors (24-26) although a putative role in conditioning response to treatments has been reported in vitro (27).…”
Section: Molecular Pathology Of Alk-rearranged Nsclcmentioning
confidence: 99%
“…Also Ou et al recently reported that the emergence of ALK -resistant mutations occurred more commonly in patients with variant 3 EML4-ALK rearrangement than in patients with variant 1 tumors [4]. Other rarer ALK fusions occur such as KIF5B-ALK [5], KLC1-ALK [6], and ALK-PTPN3 [7], but they collectively are less frequent than the ALK-EML4 rearrangement [8], and therefore little is known about their clinical significance with respects to different response to ALK TKIs. In general, patients with ALK -rearranged NSCLC tend to be younger, never smokers, and have lung adenocarcinoma, though rarely patients with other lung cancer histologies have also been found to harbor this mutation [9].…”
Section: Introductionmentioning
confidence: 99%